Oxygen-rich engineering of lignin-derived porous carbons through potassium activation for zinc ion hybrid capacitors - Xueyi Liang; Caiwei Wang; Zicheng Li; Bo Chen; Xuemin Cui; Yuanyuan Ge; Zhili Li (Resources Chemicals and Materials)
Oxygen-rich porous carbons are promising candidates for the carbon-based cathodes of zinc ion hybrid capacitors (ZIHCs). Potassium activation is a traditional and effective way to prepare oxygen-rich porous carbons. Efficient potassium activation is the key to develop high-performance oxygen-rich porous carbon cathodes. Herein, the alkali lignin, extracted from eucalyptus wood by geopolymer-assisted low-alkali pretreatment, is used to prepare oxygen-rich lignin-derived porous carbons (OLPCs) through KOH activation and K2CO3 activation at 700–900 °C. KOH activation constructs a hierarchical micro-mesoporous structure, while K2CO3 activation constructs a microporous structure. Furthermore, K2CO3 activation could more efficiently construct active oxygen (C = O) species than KOH activation. The OLPCs prepared by KOH/K2CO3 activations at 800 °C show the highest microporosity (78.4/87.7 %) and C = O content (5.3/8.0 at.%). Due to that C = O and micropore adsorb zinc ions, the OLPCs prepared by K2CO3 activation at 800 °C with higher C = O content and microporosity deliver superior capacitive performance (256 F g-1 at 0.1 A g-1) than that by KOH activation at 800 °C (224 F g-1 at 0.1 A g-1), and excellent cycling stability. This work provides a new insight into the sustainable preparation of oxygen-rich porous carbon cathodes through efficient potassium activation for ZIHCs.